Evaluation of three concentration of centrifuged egg yolk in the cryopreservation of bovine semen - Montoya-Páez, Juan David (2020)
The aim of this study was to evaluate three concentrations of centrifuged egg yolk in a commercial diluent for bovine semen. Ejaculates from four bulls were obtained and semen collections were made by electroejaculation and artificial vagina. The sperm obtained were divided into three aliquots supplemented with 10, 20 and 30% centrifuged egg yolk (YHC). Semen freezing was done in 0.5 ml straws. Thawed semen was evaluated for total (MT) and progressive motility (MP), vitality (VE), abnormal morphology (MA) and plasma membrane integrity (MI). Statistical analysis was performed by adjusting generalized linear models (GLM) and comparing means by the Tukey test. No significant differences were found for MT, VE, MA and IM between treatments, but there were significant differences for treatment with 10% YHC supplementation for linear (VSL), curvilinear (VCL) and mean (VAP) speeds with respect to 20 and 30% of YHC (p<0.05). It is concluded that using 10% YHC for cryopreservation of bovine semen improves the velocity of the spermatozoa and favours the preparation of the extender for cryopreservation of cells.